Reconstructive Osteotomy for Ankle Malunion Improves Patient Satisfaction and Function - Fumiaki Inori; Masahiko Tohyama; Hiroyuki Yasuda; Sadahiko Konishi; Akeo Waseda (Case Reports in Orthopedics)
Treatment of chronic symptoms caused by a malunion is a difficult problem in orthopedic surgery. We encountered a case of ankle malunion at our hospital about 1 year after the first operation. The patient had been unable to walk with weight-bearing but regained the ability to walk after reconstructive osteotomy of the fibula. Functional scores for the foot and ankle were significantly improved after intervention. Reconstructive osteotomy appears to represent a good option for ankle malunion.